Bowel Evisceration through Vaginal Vault Following Vaginal Hysterectomy - A Case Report - Arumugam, Sendhil Coumary; Reddi, Rani (Indian Journal of Case Reports, 2017)
Bowel evisceration through vaginal vault is a rare but serious complication of pelvic surgery specifically hysterectomy. It represents a surgical emergency and is associated with significant morbidity. Small bowel is the most common viscous to eviscerate. The present case is report of small bowel evisceration through vaginal vault in the immediate post-operative period managed vaginally.Bowel evisceration through vaginal vault following vaginal cuff dehiscence is a rare and serious complication of pelvic surgery; specifically, hysterectomy. Small bowel is the most common viscous to eviscerate. Bowel evisceration is usually managed abdominally either laparoscopically or by a laparotomy. We present a case of small bowel evisceration through vaginal vault in the immediate post-operative period which was managed vaginally.